Pengaruh Pola Asuh Orang Tua Terhadap Kestabilan Emosi Siswa Pada Mata Pelajaran Ilmu Pengetahuan Sosial - Novitasari, Nora Indah; riyadi, Riyadi; ., Ali Imron; Setyawan, Katon Galih (Jurnal Dialektika Pendidikan IPS, 2023)
This study aims to determine whether there is influence and to find out how much influence parenting styles have on students’ emotional stability in Social Science Subjects. This study uses quantitative research methods with sample selection using purposive sampling technique. The researcher chose class VII H, which consisted of 30 students to be given a parenting and emotional stability questionnaire. The findings in this study indicate that Class VII H has a moderate level of parenting with authoritarian parenting as much as 7%, democratic 37%, negligent 3% and for permissive parenting as much as 17%. The level of emotional stability in this class is in the high category as much as 6.66%, as much as 83.33% and as low as 10%. The hypothesis test uses the Kolmogorof Sminorv test with a significance value of 0.200 with a significance level of 0.05. This means that this research is significant and the closeness test gets a 15% effect which is included in the very low category. Overall, there is an influence between parenting styles on students’ emotional stability in Social Science Subjects.